Stabilization of spherically symmetric static Boson stars by Coleman-Weinberg self-interaction potential - Firoozeh Eidizadeh; Hossein Ghaffarnejad (Nuclear Physics B)
Our motivation in this work is due to the great importance of relativistic boson stars as fierce competitors of black holes. From theoretical perspective, they described by complex Klein Gordon (KG) scalar fields interacting with curved background in general form. In this work we use the Einstein-Klein Gordon (EKG) scalar tensor gravity in presence of the Coleman-Weinberg (CW) self-interaction potential to study formation of a spherically symmetric boson star and situation of its stability. We choose the CW potential because of its important role in description of cosmic inflation.